PHYSICOCHEMICAL, PRELIMINARY PHYTOCHEMICAL ANALYSIS AND ANTIBACTERIAL ACTIVITY AGAINST CLINICAL PATHOGENS OF MEDICINALLY IMPORTANT ORCHID GEODORUM DENSIFLORUM (LAM) SCHLTR - Keerthiga, M.; Anand, S. P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To evaluate the Physicochemical, Preliminary Phytochemical analysis and Antibacterial activity of Geodorum densiflorum against clinical pathogens and to prove the orchid will target to meet the therapeutic demands. Methods: The physicochemical parameters and Preliminary Phytochemical analysis of the orchid were studied. The antibacterial properties using the following bacterial strains, ie., Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Streptococcus pyogenes, Klebseilla pneumoniea, Pseudomonas aeruginosa were studied. Streptomycin were used as a control and study was conducted using disc diffusion method and the MIC value also be evaluated. Results: The Physicochemical parameters show the presence of bioactive compounds. The phytochemical screening revealed the presence of Alkaloids, Tannins, Flavonoids, Sopanins, Steroid and Terpenoids. The ethanol extract showed significant total activity against Staphylococcus aureus than other extracts. Conclusion: The ethanol extract of Geodorum densiflorum can successfully used as a pharmaceutical agents as antibacterial drug.